International criminal justice after World War II - Jovašević Dragan (Војно дело, 2015)
This year marks the seventieth anniversary of the end of the most terrible war in the history of mankind. Namely, after six years of worldwide hostilities, the Nazi and fascist countries, primarily Germany and Japan, finally signed the capitulation. This ended the state of war, but the assessment of the true scale of this human tragedy continued for years later. In this light also the operation of international judicial bodies - the international military tribunals in Nuremberg and Tokyo - should be seen, where the criminal responsibility was judged and, for the first time in the history of human civilization, punishments were pronounced and enforced to perpetrators of the most serious international crimes committed during war operations, especially against civilians and prisoners of war.